KENDALA-KENDALA PENGUASAAN BAHASA MELAYU STANDARD DALAM KALANGAN PELAJAR MELAYU DI SEKOLAH PONDOK DI PATANI, THAILAND - Phaosan Jehwae (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
Language represents the nation. From language expressed, the one can know from the community where they came from. Therefore, language is one of the nation's character -forming which should be maintained. If the mother tongue is missing, the nation will lose its identity. In the case of Patani Malay community in Thailand, the mastery of Malay increasingly eroded. As an ethnic minority, politically they were driven by Thailand's national language. Moreover, the Malay language is not used as the language of instruction and official language of science in Thailand. In fact, the Malay vocabulary began to lose its original meaning because of the interaction between this language and other foreign languages. This article shows the negative impact of all of these conditions on the mastery of the standard Malay for the educated Malays in Thailand. In general, the Malay students in Thailand is not much else to master Malay Standard.